Overview of Depression Level in Knee Osteoarthritis Patients in Geriatric Polyclinic in General Hospital - Fadilah, Rakha Ariq; Yanto, Arief; Mubin, Mohammad Fatkhul; Rahayu, Desi Ariyana (Media Keperawatan Indonesia, 2024)
Knee osteoarthritis (OA) is one of the most prevalent degenerative conditions among the elderly, significantly impacting both mental and physical health, including an elevated risk of depression. This study aims to assess the prevalence of depression distribution among patients with knee osteoarthritis attending the geriatric polyclinic at a Regional General Hospital in Indonesia. A descriptive cross-sectional study design was employed. Data were collected through medical record reviews and structured interviews. The findings revealed that 61.3% of patients experienced mild depression, 35.3% were categorized as having no depression, and 3.3% had moderate depression, with no cases of severe depression identified. The majority of patients were classified as older adults (aged 75–90 years, 60%) and predominantly female (78.7%). In conclusion, knee osteoarthritis is most commonly observed in the older age group and among females. Most patients present with mild depression, which tends to worsen with advancing age, influenced by chronic pain and functional limitations.